At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the system of equations by substitution, we'll follow these steps:
Given the system:
[tex]\[ \begin{aligned} -x - 9y &= -19 \\ y &= 6x - 4 \end{aligned} \][/tex]
1. Substitute the expression for [tex]\( y \)[/tex] from the second equation into the first equation:
From the second equation, we have:
[tex]\[ y = 6x - 4 \][/tex]
Now, substitute this value into the first equation:
[tex]\[ -x - 9(6x - 4) = -19 \][/tex]
2. Simplify the equation:
Distribute the [tex]\(-9\)[/tex] through the terms inside the parentheses:
[tex]\[ -x - 54x + 36 = -19 \][/tex]
Combine like terms:
[tex]\[ -55x + 36 = -19 \][/tex]
3. Isolate [tex]\( x \)[/tex]:
Move the constant term to the other side by subtracting 36 from both sides:
[tex]\[ -55x = -19 - 36 \][/tex]
Which simplifies to:
[tex]\[ -55x = -55 \][/tex]
Divide both sides by [tex]\(-55\)[/tex]:
[tex]\[ x = 1 \][/tex]
4. Substitute [tex]\( x = 1 \)[/tex] back into the second equation to find [tex]\( y \)[/tex]:
Use the expression for [tex]\( y \)[/tex] from the second equation:
[tex]\[ y = 6(1) - 4 \][/tex]
Simplify:
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ x = 1 \quad \text{and} \quad y = 2 \][/tex]
These values satisfy both original equations, so the system is consistent and the solution is [tex]\((1, 2)\)[/tex].
Given the system:
[tex]\[ \begin{aligned} -x - 9y &= -19 \\ y &= 6x - 4 \end{aligned} \][/tex]
1. Substitute the expression for [tex]\( y \)[/tex] from the second equation into the first equation:
From the second equation, we have:
[tex]\[ y = 6x - 4 \][/tex]
Now, substitute this value into the first equation:
[tex]\[ -x - 9(6x - 4) = -19 \][/tex]
2. Simplify the equation:
Distribute the [tex]\(-9\)[/tex] through the terms inside the parentheses:
[tex]\[ -x - 54x + 36 = -19 \][/tex]
Combine like terms:
[tex]\[ -55x + 36 = -19 \][/tex]
3. Isolate [tex]\( x \)[/tex]:
Move the constant term to the other side by subtracting 36 from both sides:
[tex]\[ -55x = -19 - 36 \][/tex]
Which simplifies to:
[tex]\[ -55x = -55 \][/tex]
Divide both sides by [tex]\(-55\)[/tex]:
[tex]\[ x = 1 \][/tex]
4. Substitute [tex]\( x = 1 \)[/tex] back into the second equation to find [tex]\( y \)[/tex]:
Use the expression for [tex]\( y \)[/tex] from the second equation:
[tex]\[ y = 6(1) - 4 \][/tex]
Simplify:
[tex]\[ y = 6 - 4 \][/tex]
[tex]\[ y = 2 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\[ x = 1 \quad \text{and} \quad y = 2 \][/tex]
These values satisfy both original equations, so the system is consistent and the solution is [tex]\((1, 2)\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.